Influence of the medium (strongly acid or basic) over the electrochemical properties of the nitrate selective electrode - Del Tóro Déniz, Rubén; M. Rajmanko, E.; Peón Espinosa, Ana María; Peña Velázquez, Inés (Eclética Química, 1997)
A nitrate selective electrode was prepared for use in an aggresive medium (high acidic or basic concentration). It is demonstrated that the depending E graph with respect to pNO3- has not a Nernstian response in concentration acidic range upper 0.1 mol/L H2SO4. The observed behaviour is supposed to be due to the formation of a dimeric anion HN2O6-.